Implications for the metabolic fate of oral glutamine supplementation within plasma and erythrocytes of patients with sickle cell disease: A pharmacokinetics study. (March 2022) - Morris, Claudia R.; Kuypers, Frans A.; Hagar, Robert; Larkin, Sandra; Lavrisha, Lisa; Saulys, Augusta; Vichinsky, Elliott P.; Suh, Jung H.
Abstract: Objectives: L -Glutamine is FDA-approved for sickle cell disease (SCD), yet the mechanism(s)-of-action are poorly understood. We performed a pharmacokinetics (pK) study to determine the metabolic fate of glutamine supplementation on plasma and erythrocyte amino acids in patients with SCD. Design: A pK study was performed where patients with SCD fasting for > 8 h received oral L -glutamine (10 g). Blood was analyzed at baseline, 30/60/90 min/2/3/4/8 hrs. A standardized diet was administered to all participants at 3 established time-points (after 2/5/7hrs). A subset of patients also had pK studies performed without glutamine supplementation to follow normal diurnal fluctuations in amino acids. Setting: Comprehensive SCD Center in Oakland, California Results: Five patients with SCD were included, three of whom performed pK studies both with and without glutamine supplementation. Average age was 50.6 ± 5.6 years, 60% were female, 40% SS, 60% SC. Plasma glutamine levels increased significantly after oral glutamine supplementation, compared to minimal fluctuations with diet. Plasma glutamine concentration peaked within 30-min of ingestion ( p  =  0.01 ) before decreasing to a plateau by 2-h that remained higher than baseline by 8 h. Oral glutamine also increased plasma arginine concentration, which peaked by 4-h ( p  =  0.03 ) and remained elevated through 8-h. Erythrocyte glutamine levels began to increase by 8-h, while erythrocyte arginine concentration peaked at 4-h. Conclusions: Oral glutamine supplementation acutely improved glutamine and arginine bioavailability in both plasma and erythrocytes. This is the first study to demonstrate that glutamine therapy increases arginine bioavailability and may provide insight into shared mechanisms-of-action between these conditionally-essential amino acids. Highlights: Mechanism(s)-of-action for FDA-approved oral L -glutamine to treat SCD are unknown. Oral glutamine rapidly increases plasma glutamine concentration within 30 min of supplementation in patients with SCD. A 10-gram dose of oral glutamine increases both glutamine and arginine bioavailability.